Medicinals teas - Lopes, Cleuza Francisca da Silva; Lima , Maria dos Santos; Signorini, Márcia Cristina Gonçalves; Simião, Regina Aparecida Versoza; Guimarães , Renata Maria de Souza; Cervelati , Sabrina Ferro (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf